Adaptive feedback linearizing control of linear induction motor considering the end-effects. (October 2016) - Alonge, Francesco; Cirrincione, Maurizio; D'Ippolito, Filippo; Pucci, Marcello; Sferlazza, Antonino
Abstract: This paper proposes an input–output feedback linearization techniques for linear induction motors, taking into consideration the dynamic end-effects. As a main original content, this work proposes a new control law based on the on-line estimation of the induced-part time constant. The estimation law is obtained thanks to a Lyapunov based analysis and thus the stability of the entire control system, including the estimation algorithm, is intrinsically guaranteed. Moreover, with such an approach even the on-line variation of the induced-part time constant with the speed is retrieved, thus improving the behavior of previously developed approaches where such a variation vs. speed is considered a priori known. The proposed control technique, integrating the on-line induced-part time constant estimation, is tested by means of simulations and experiments carried out on a suitably developed test set-up. Abstract : Highlights: An adaptive input–output feedback linearization techniques for linear induction motors has been proposed. The control law is based on the on-line estimation of the induced-part time constant. The stability of the entire control system is demonstrated thanks to a Lyapunov based analysis. The proposed control technique has been tested by means of simulations and experiments carried out on a suitably developed test set-up.